Melawan Fundamentalisme: Memanusiakan Perempuan - Siti Musdah Mulia (AL-KAINAH: Journal of Islamic Studies, 2022)
By reason of purification of religion and return to the text of the Qur'an and Hadith, Islamic fundamentalism emphasizes the difference in rights between men and women. According to them, God deliberately made the two different and the difference was not discrimination but for the sake of human happiness. Fundamentalism calls for a return to religion. However, in the context of women, what is claimed to be a return to religious teachings is to return home to women; back to the domestication of women. In short, fundamentalism proclaims the politics of anti-feminism, anti-pluralism, and anti-humanism. The anti-feminist politics that became the icon of the fundamentalism movement is the most successful program in many Islamic areas, including in Indonesia. Fundamentalists from various religions have the same tendency, namely to manipulate and use religious teachings to legitimize patriarchal power, as well as marginalize women. Therefore, the view of fundamentalism that is not accommodating to human values ​​and at the same time not friendly to women must be seriously and systematically eliminated. Our goal is none other than to humanize women, and to build a just and civilized civil society.